The Length of Bones of Upper and Lower Extremities in Turkish Society Antropometrical Search - Günay, Yasemin; Özden, Hilmi; Çetin, Gürsel (The Bulletin of Legal Medicine, 2001)
The purpose of this study is to make a contribution to the formation of a database regarding the identification from the skeletal bones spesific to the Turkish Community. The skeletal bones sent to the State Institute of Forensic Medicine were used for this purpose. Measurements consistent with the international standards were obtained from femur, tibia, fibula, humerus, radius and ulna. Statistically significant differences were found between all upper extremity bone mesaurements with maximum length of the femur, bicondylar length of the femur, epicondylar breadth of the femur, length of the tibia, maximum epiphyseal breadth of the proximal tibia, A-P breadth of the corpus tibia, circumference of the tibia at the nutrient foramen and length of the fibula that belongs to lower extremity with respect to sex (Student’s t-test p
Keywords: forensic anthropology; turkish community; femur; tibia; fibula; humerus; ulna; radius